Un aspect crucial mais délicat des libertés de conscience et de religion des articles 2 et 3 des Chartes canadienne et québécoise: l'objection de conscience - Brun, Henri (Les Cahiers de droit, 1987)
The Supreme Court of Canada, obiter, in the Big M Drug Mart Case, has spoken of the "Constitutional Exemption". It is the possibility not to be bound to obey the neutral laws that conflict with one's conscience or religion. It is what we call in French l'objection de conscience. The institution exists in Canadian and Québec Law as a part of the right to freedom of conscience or religion expressed in 2a) and 3 of the Canadian and Québec Charters of Rights. And it goes well beyond the right not to fight within the armed forces. The Supreme Court of Canada has actually delivered six judgments touching on the subject in 1985 and 1986. The conditions under which l'objection de conscience come into play are not so well known however. Does it cover matters of worship or only rules of morals ? Secular or only religious principles ? Personal or only group beliefs ? Do the existence of the rule, the sincerity of the objector and the reasonableness of the exemption have to be proved? Above all, what is the difference between a creed and an opinion ? The following article tries to formulate answers to these questions, with the help of current case-law.